Approaches to improve the quality of education and social life in the Russian Federation - Tat'yana V. Solov'eva; Dinara A. Bistyajkina; Elena G. Pan'kova; Ol'ga M. Lizina (Revista on line de Política e Gestão Educacional)
The relevance of the given problem is determined by the need of studying the transforming system of education and social protection of war veterans and senior citizens in the framework of changing social and economic conditions, which is particularly significant during the process of increasing social threats. The purpose of the work is to study the Russian experience to improve the quality of life and education of veterans and senior citizens in the framework of the modern conditions and develop recommendations for improving the quality of life of the investigated category. The principal method of studying this problem is the system (integrative) method which demands the analysis of social, economic, legal, and other supportive measures for the veterans and senior citizens. The sociological method of the research is an expert survey. The study has concluded that is vital to improve the practice of interdepartmental interaction in the development of various technologies and educational means of social services. The practical significance of the study is the possible use of the developed recommendations in the framework of social gerontology and practical activities of institutions of the social protection of senior citizens; moreover, the study results can be useful both to the experts in social security and social welfare, and the general public.